Hubungan Asupan Gizi Makro Terhadap Status Gizi Balita Stunting di Wilayah Pesisir Kota Kendari - Sumarti, Sumarti; Salma, Wa Ode; Binekada, Made Chriastian (Jurnal Gizi Ilmiah, 2024)
Stunting is a major nutritional problem in Indonesia that can determine the quality of resources. Stunting children are susceptible to disease, have difficulty in physical and cognitive development, and are at risk of developing degenerative diseases as adults. The prevalence of stunting in 2021 was 0.95%, 2022 was 1.4% and 2023 was 1.69%. The purpose of this study was to determine the relationship between macro nutrient intake to the nutritional status of Stunting Toddlers in the Coastal Area of ​​Kendari City. This type of research is quantitative, Cross Sectional Study design. The population in this study were all toddlers in the working area of ​​the Mata, Benu-Benua and Abeli ​​Health Centers for the period January 2024, totaling 4,272 people and the sample in this study was part of the toddlers in the period January 2024 in the working area of ​​the Mata, Benu-Benua and Abeli ​​Health Centers, totaling 98 people. The sampling technique used proportional stratified random sampling. Data analysis used the chi-square test. The results of the chi-square test at a 95% confidence level, obtained p value of 0.000 for carbohydrate, protein, and fat intake. The conclusion of this study is that there is a relationship between macronutrient intake (KH, Protein and Fat) with the incidence of stunting in toddlers in the coastal areas of Kendari City